The application of jigsaw cooperative learning model on the reaction rate material to train students metacognitive skills - Dini Madiar; Utiya Azizah (Jurnal Pijar Mipa, 2022)
This study aims to describe the implementation of the Jigsaw type cooperative learning model, student activities in the application of learning models, students' metacognitive skills, and student responses to the applied learning model. This research targets 34 students of class XI MIPA 5 SMAN 19 Surabaya with a One Group Pretest Posttest Design research design. The results obtained are 1) the learning model implementation obtained 96.42% and 99.52% with very good criteria. 2) The percentage of relevant student activities is greater than that of irrelevant students, namely 98.98% and 96.59%. 3) The students' metacognitive skills increased with the average gain score obtained belonging to the high criteria, including Planning Skills 0.90; Monitoring skills 0.82; and Evaluating skills 0.83. 4) Students' response to the applied learning model is good, where 93.3% of students respond positively.